The Chemical and Antibacterial Evaluation of St. John's Wort Oil Macerates Used in Kosovar Traditional Medicine - Lyles, James T.; Kim, Austin; Nelson, Kate; Bullard-Roberts, Angelle L.; Hajdari, Avni; Mustafa, Behxhet; Quave, Cassandra L. (Frontiers in Microbiology, 2017)
Hypericum perforatum L. (Hypericaceae), or St. John’s Wort, is a well-known medicinal herb often associated with the treatment of anxiety and depression. Additionally, an oil macerate (Oleum Hyperici) of its flowering aerial parts is widely used in traditional medicine across the Balkans as a topical wound and ulcer salve. Other studies have shown that Oleum Hyperici reduces both wound size and healing time. Of its active constituents, the naphthodianthrone hypericin and phloroglucinol hyperforin are effective antibacterial compounds against various Gram-positive bacteria. However, hyperforin is unstable with light and heat, and thus should not be present in the light-aged oil macerate. Additionally, hypericin can cause phototoxic skin reactions if ingested or absorbed into the skin. Therefore, the established chemistry presents a paradox for this H. perforatum oil macerate: the hyperforin responsible for the antibacterial bioactivity should degrade in the sunlight as the traditional oil is prepared; alternately, if hypericin is present in established bioactive levels, then the oil macerate should cause photosensitivity, yet none is reported. In this research, various extracts of H. perforatum were compared to traditional oil macerates with regards to chemical composition and antibacterial activity (inhibition of growth, biofilm formation, and quorum sensing) versus several strains of Staphylococcus aureus in order to better understand this traditional medicine. It was found that four Kosovar-crafted oil macerates were effective at inhibiting biofilm formation (MBIC50 active range of 0.004 – 0.016% v/v), exhibited moderate inhibition of quorum sensing (QSIC50 active range of 0.064 – 0.512% v/v), and contained detectable amounts of hyperforin, but not hypericin. Overall, levels of hypericin were much higher in the organic extracts, and these also exhibited more potent growth inhibitory activity. In conclusion, these data confirm that oil macerates employed in traditional treatments of skin infection lack the compound credited with phototoxic reactions in H. perforatum use and exhibit anti-biofilm and modest quorum quenching effects, rather than growth inhibitory properties against S. aureus.